Strategies and Challenges in Enhancing Critical Thinking for Writing Descriptive Text - Syifa Ul Aini; Misya Niftalia; Husnul Khatimah; Nifyatul Ahya; Risa Miranti; Widyawati Widyawati; Misnawati Misnawati (Journal of English Language and Education, 2026)
Critical thinking is one of the essential learning outcomes in Education, particularly in enhancing students’ writing ability. However, many students still face difficulties in applying critical thinking in writing descriptive text, especially in generating and organizing ideas. This research investigates the effectiveness of various strategies and identifies challenges in enhancing students’ critical thinking in writing descriptive text. This study employed a qualitative descriptive approach, with data collected through classroom observation and writing tests. The findings revealed that the lecturer need to prioritize interactive approaches to foster critical thinking. The main challenges included limited vocabulary, difficulty in generating ideas, lack of coherence, grammatical errors, and unclear ideas. These strategies applied included encouraging reading, providing visual aids, and implementing innovative teaching methods. The mean score of tests was 64.94%, it is indicated students’ difficulties. This study concluded that the effective strategies can improve students’ critical thinking in writing descriptive text.